Molecular epidemiology of multiple endocrine neoplasia 2: implications for RET screening in the new millenium - Machens, Andreas; Lorenz, Kerstin; Sekulla, Carsten; Höppner, Wolfgang; Frank-Raue, Karin; Raue, Friedhelm; Dralle, Henning (European journal of endocrinology, 2013)
Twenty years ago, the groundbreaking discovery that rearranged during transfection (RET) mutations underlie multiple endocrine neoplasia 2 (MEN2) and familial medullary thyroid cancer (FMTC) ushered in the era of personalized medicine. MEN2-associated signs, taking time to manifest, can be subtle. This study sought to clarify to what extent conventional estimates of 1:200000-500000 underestimate the incidence of RET mutations in the population.Included in this retrospective investigation were 333 RET carriers born between 1951 and 2000 and operated on at the largest German surgical referral center (286 carriers) or elsewhere (47 carriers).To estimate the incidence of RET mutations, the number of RET carriers born in Germany in five decades (1951-1960, 1961-1970, 1971-1980, 1981-1990, and 1991-2000) was divided by the corresponding number of German live births.Owing to improved diagnosis and capture of FMTC and MEN2 patients, minimum incidence estimates increased over time: overall from 5.0 (1951-1960) to 9.9 (1991-2000) per million live births and year (P=0.008), and by American Thyroid Association/ATA class from 1.7 to 3.7 for ATA class C (P=0.008); from 1.8 to 2.7 for ATA class A (P=0.017); from 1.5 to 2.2 for ATA class B (P=0.20); and from 0 to 1.4 for ATA class D mutations per million live births and year (P=0.008). Based on 1991-2000 incidence estimates the prevalence in Germany is ∼1:80000 inhabitants.The molecular minimum incidence estimate of ≈1:100000 was two- to fivefold greater than conventional estimates of 1:200000-500000.
Gesehen am 15.04.2025